Studies on Chick Embryo Thrombocytes - Stalsberg, Helge; Prydz, Hans (Thrombosis and Haemostasis, 1963)
The formation of hemostatic plugs were studied in the chick embryo through in vivo microscopy, in sections of hemostatic plugs and by measurements of primary bleeding time. Thrombocytes were found to be their only cellular constituent. Ability to form adequate hemostatic plugs appeared rather abruptly in embryos of stages 16-17 and coincided with an increase in thrombocyte precursors (stages III and IV).The thrombocytes initially adhere to the cut edge of the vessel. The extension of the hemostatic plug into the vessel lumen is a secondary step in plug development.